Mixed sneutrino dark matter in light of the 2011 XENON and LHC results - Dumont, Béranger; Bélanger, Geneviève; Fichet, Sylvain; Kraml, Sabine; Schwetz, Thomas (Journal of cosmology and astroparticle physics, 2012)
In the context of supersymmetric models in which small Dirac neutrino masses are generated by supersymmetry breaking, a mainly right-handed (RH) mixed sneutrino can be an excellent cold dark matter (DM) candidate. We perform a global analysis of the Minimal Supersymmetric Standard Model (MSSM)+RH neutrino parameter space by means of Markov Chain Monte Carlo sampling. We include all relevant constraints from collider and dark matter searches, paying particular attention to nuclear and astrophysical uncertainties. Two distinct cases can satisfy all constraints: heavy sneutrino DM with mass of order 100 GeV, as well as light sneutrino DM with mass of about 3-6 GeV. We discuss the implications for direct and indirect dark matter searches, as well as for SUSY and Higgs searches at the LHC for both, the light and the heavy sneutrino dark matter case. The light sneutrino case is excluded by the 125-126 GeV Higgs signal.